A serdülők valóságkonstrukciója, az önészlelés problémája és a lelkigondozó életértelmezés - KOVÁCS, Szabolcs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
The Construction of Reality by the Teenagers, the Problem of Self-sense and the Pastoral Interpretation of Life The systemic therapy and spiritual counselling have recognized the fact that a system cannot change its dynamic: an outer effect is needed. The paradigm has correlation with the Christian soteriology: we need a Redeemer, we cannot be our own saviour. The perspective of „step out the box” paradigm put an accent on our attitude of being vigilant on what is coming toward us from the outside. This may bring the possibility of change to us. The teaching ambition, the writings and professional visions of Gábor Hezser made us to be open for comparing the usual with the new idea. A new perspective brings new ideas, motivates and moves a step further… This work is a short resume about the spiritual counselling work, which works slowly, through short steps and tenuity to strengthen all those who need a helping hand.